2016
DOI: 10.1016/j.cma.2015.11.028
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian–Eulerian finite element algorithm for advection–diffusion–reaction problems with phase change

Abstract: This paper presents a particle-based Lagrangian-Eulerian algorithm for the solution of the unsteady advectiondiffusion-reaction heat transfer equation with phase change. The algorithm combines a Lagrangian formulation for the advection + reaction problem with the Eulerian-based heat source method for the diffusion + phase change problem. The coupling between the Lagrangian and Eulerian subproblems is achieved with a phase change detector scheme based on a local latent heat balance and a consistent/conservative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Given the presence of sharp gradients and the need to advect them over many time steps, an accurate and stable advection-diffusion algorithm is required to avoid numerical oscillations or excessive numerical diffusion. Here we use the particle-based Lagrangian-Eulerian formulation of (Oliveira et al, 2016), which combines a Lagrangian formulation for the advective part and an Eulerian-based heat source method for the diffusion and heat sources.…”
Section: Thermal Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the presence of sharp gradients and the need to advect them over many time steps, an accurate and stable advection-diffusion algorithm is required to avoid numerical oscillations or excessive numerical diffusion. Here we use the particle-based Lagrangian-Eulerian formulation of (Oliveira et al, 2016), which combines a Lagrangian formulation for the advective part and an Eulerian-based heat source method for the diffusion and heat sources.…”
Section: Thermal Problemmentioning
confidence: 99%
“…We have also designed an effective interpolation scheme to transfer temperature information from nodes to particles and back at every time step. (Oliveira et al, 2016) showed that the method is high-order, accurate, oscillation-free and applicable to a wide range of fully-coupled advection-diffusion-reaction problems (see Appendix C).…”
Section: Thermal Problemmentioning
confidence: 99%
“…Oñate presents the solution by a stabilized FEM via the finite calculus method . Oliveira presents a particle‐based Lagrangian‐Eulerian FEM algorithm for the unsteady ADR problems considering the phase change . Kaya proposes a finite difference scheme for multidimensional steady and unsteady convection‐diffusion‐reaction problems .…”
Section: Introductionmentioning
confidence: 99%
“…Recent years, the Lagrangian-Eulerian (LE) approaches with the combination of Lagrangian particles and the Eulerian background grids have attracted great attention in solving the convectiondiffusion problems [20][21][22][23][24] . The LE method takes advantage of appropriate operator splitting techniques to solve different aspects of the physical model with most suitable Lagrangian or Eulerian formalism [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The LE method takes advantage of appropriate operator splitting techniques to solve different aspects of the physical model with most suitable Lagrangian or Eulerian formalism [24] . Shipilova et al [25] applied a LE method (the particle transform method) to solve the convection-diffusion-reaction problems, numerical results showed that the PTM can avoid the numerical oscillation even for a very sparse grid.…”
Section: Introductionmentioning
confidence: 99%